2024
DOI: 10.1037/cbs0000337
|View full text |Cite
|
Sign up to set email alerts
|

False impressions? The effect of language proficiency on cues, perceptions, and lie detection.

Abstract: We examined how observers’ impressions of nonnative speakers and their cues to deception affected decision-making. Native and nonnative English speakers lied or told the truth about having committed a transgression, and then observers attempted to detect their lies. Observers were better able to discriminate between lie- and truth-telling native speakers than nonnative speakers. They also held more positive impressions of native speakers than nonnative speakers. Unlike observers, trained coders identified a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(106 reference statements)
1
0
0
Order By: Relevance
“…In other words, beginner English speakers were judged differently relative to their more proficient counterparts. Although we expected native observers to judge native speakers more favorably, our results partially replicated Bond and Atoum (2000) and Elliott and Leach (2022), who found that observers demonstrated a truth bias toward non-native speakers. Bond and Atoum attributed this finding to observers automatically giving low-proficiency speakers the benefit of the doubt, resulting in lower discrimination ability.…”
Section: Discussionsupporting
confidence: 83%
“…In other words, beginner English speakers were judged differently relative to their more proficient counterparts. Although we expected native observers to judge native speakers more favorably, our results partially replicated Bond and Atoum (2000) and Elliott and Leach (2022), who found that observers demonstrated a truth bias toward non-native speakers. Bond and Atoum attributed this finding to observers automatically giving low-proficiency speakers the benefit of the doubt, resulting in lower discrimination ability.…”
Section: Discussionsupporting
confidence: 83%